Correspondence of Richardson's final years (1755-1761) - Richardson, Samuel 1689-1761 (Cambridge University Press, 2019)
Samuel Richardson (1689-1761) was a prominent eighteenth-century printer and businessman as well as an important and influential English novelist. He was also a prolific letter writer. This volume in the first ever full edition of Richardson's correspondence offers a fascinating glimpse of the writer in his final years - at the height of his professional powers but facing the challenging circumstances of physical decline and commercial conflict. The collection of miscellaneous letters addresses a variety of issues ranging from details of Richardson's printing operation to his mentorship of women writers including Sarah Fielding, Anna Meades and Frances Sheridan. Other correspondents of note include Samuel Johnson, Meta Klopstock, Thomas Sheridan and Tobias Smollett. Taken together this series of letters draws an intimate picture of Richardson's professional and personal circles as they exchange family gossip, business advice, literary anecdotes and news of the day